Logistics 4.0 and Sustainable Supply Chain Management: Innovative Solutions for Logistics and Sustainable Supply Chain Management in the Context of Industry 4.0 - Carlos Jahn; Wolfgang Kersten; Christian M. Ringle (epubli GmbH, 2018)
This volume contains research contributions by an international group of authors addressing innovative and technology-based approaches for logistics and sustainability. They present simulation studies, systems and models for optimizations and digitalized solutions with a focus on maritime as well port and city logistics. This volume, edited by Carlos Jahn, Wolfgang Kersten, and Christian Ringle, provides valuable insights into Logistics 4.0 and Sustainable Supply Chain Management with regard to: Maritime and Port Logistics, City Logistics, Sustainability.
urn:nbn:de:gbv:830-88223163; https://econpapers.repec.org/RePEc:zbw:hiclch:209356; https://econpapers.repec.org/RePEc:zbw:hiclch:209357; https://econpapers.repec.org/RePEc:zbw:hiclch:209358; https://econpapers.repec.org/RePEc:zbw:hiclch:209359; https://econpapers.repec.org/RePEc:zbw:hiclch:209360; https://econpapers.repec.org/RePEc:zbw:hiclch:209361; https://econpapers.repec.org/RePEc:zbw:hiclch:209362; https://econpapers.repec.org/RePEc:zbw:hiclch:209363; https://econpapers.repec.org/RePEc:zbw:hiclch:209364; https://econpapers.repec.org/RePEc:zbw:hiclch:209365; https://econpapers.repec.org/RePEc:zbw:hiclch:209366
Keywords: 650; Supply Chain Management; Logistics; Sustainability; Digitalization